Interrelations between strategic orientation, knowledge management, innovation and performance. Empirical findings from a national survey in Germany. (1st January 2012) - Pawlowsky, Peter; Schmid, Simone
Our research interest is to examine the interrelations of strategic orientation, knowledge management (KM), innovation and performance. To analyse this interplay, we primarily consult the knowledge based view ( KBV ) of the firm in combination with the concept of organisational ambidexterity. Our empirical data has been generated by a national survey, where senior management executives of 2, 933 German companies have been asked for self-ratings, which we analysed with the help of structural equation modelling (SEM). Accordingly, our results allow for a discussion of rare generalisable data and results. Our findings indicate that both market and resource orientation show a moderate positive impact on KM. We can confirm a strong positive relationship between KM and innovation. Eventually, we can support a strong positive impact of innovation on performance. The latter has been measured by variables providing information on financial, market and motivational aspects of performance.